I have no clue with this one. Can someone help me please?

Answers

Answer #1 | 30/12 2013 05:51

If you double the first equation, then the y terms will cancel each other out when you add the equations.
6x + 4y = 8 <-- first equation doubled
5x - 4y = 3
---------------- <-- add the equations
11x = 11
Divide both sides by 11 to isolate x
x = 1 <-- answer for x
Now you can find y by subbing "1" in for "x"
3x + 2y = 4
1) Replace x with 1
3*1 + 2y = 4
same as
3 + 2y = 4
Subtract 3 from both sides
2y = 1
Divide both sides by 2
y = 1/2 <-- answer for y
Answer:
(1, 0.5)

Answer #2 | 30/12 2013 05:53

It's simple.
What you need to do is
1) Try to eliminate and of the variable (x or y).
2) We can do it by multiplying both equations by a number such that x of both or y or both become same.
eg: if we multiply eq 1 with 2
6x + 4y = 8
And equation 2 will remain same as it is.
5x-4y=3;
Now we can eliminate y by adding both of these equations.
6x + 4y + 5x - 4y = 8 + 3
11x = 11
x = 1
Put x in any of the equation and you get value of y
3x + 2y = 4
3 + 2y = 4
y = 1/2
Answer : (1,0.5)

Answer #3 | 30/12 2013 05:57

3x + 2y = 4
5x - 4y = 3
multiply first equation by 2, add to second equation:
6x + 4y = 8
5x - 4y = 3
______________
11x = 11
x = 11/11 = 1
using first equation:
3(1) + 2y = 4
2y = 1
y = 1/2
check using second equation:
5(1) - 4(1/2) = 3
5 - 2 = 3 checks
solution set: (1, 1/2) (first choice)
- .--

Answer #1| 30/12 2013 05:51